Section 504 of the Rehabilitation Act and the Right to Participate in School Athletic Programs - Carol L. Alberts (Educational Considerations, 1984)
No otherwise qualified handicapped student may be discriminated against solely on the basis of the handicap when participating in school athletic programs.